Pengaruh Konflik Peran Ganda, Work Family Conflict ,Beban Kerja Dan Stress Kerja Terhadap Kinerja Karyawati PT. Bank Negara Indonesia (Persero )Tbk Cabang Pare –Pare - Samsinar Samsinar; Nurdjanah Hamid; Wahda Rasyid (Magister Management, Hasanuddin University, 2019)
This study aims to determine the effect of multiple role conflict (work-family conflict, workload and work stress on the performance of female employees of PT. Negara Negara Indonesia (Persero) Pare-pare. The type of data collected is in the form of quantitative and qualitative data. The population of this study was all employees of the PT. Bank Negara Indonesia Branch of Pare-pare who were married and had as many as 36 children. Sampling technique uses purposive sampling. Data sources used are primary data and secondary data. Data were analyzed using path analysis. The results of this study indicate that multiple role conflict and workload directly influence significantly the work stress of female employees of PT. Bank Negara Indonesia (Persero) Tbk. The relationship between a conflict of dual roles to positive work stress and the relationship between workloads to positive work stress means that an increase in workload can increase the work stress of female employees. Direct work stress also negatively affects the performance of female employees of PT. Bank Negara Indonesia (Persero) Tbk, meaning that when work stress increases, performance will decrease